Garlic essential oil increases rates of eggs fertilization and hatching of Rhamdia quelen larvae in an artificial incubation system - Marengoni,Nilton Garcia (2017)
ABSTRACT: The objective of this study was to evaluate the effects of garlic (Allium sativum) essential oil on the rates of eggs fertilization and hatching and on the normal development of larvae of artificially incubated silver catfish (Rhamdia quelen). The experiment was carried out using a completely randomized experimental design with four treatments and five replicates. The treatments consisted of introducing garlic essential oil into the incubators, which used a closed system of water recirculation, at concentrations of 0, 1, 3, and 5mg L-1. Rates of eggs fertilization and larval hatching were determined at 10 and 24h after the beginning of eggs hydration. Morphology of larvae was assessed with the aid of a stereo microscope to determine the rate of normal development. The concentration of 5mg L-1 promoted better rates of eggs fertilization and larval hatching. Concentrations of garlic essential oil had a linear effect on eggs fertilization rates and larval hatching. Garlic oil did not influence the morphology of the larvae (P>0.05). It is recommended to use 5mg L-1 of garlic essential oil to promote better rates of eggs fertilization and larval hatching of artificially incubated silver catfish.